Digital Twins and Road Construction Using Secondary Raw Materials - Sebastjan Meža; Alenka Mauko Pranjić; Rok Vezočnik; Igor Osmokrović; Stanislav Lenart (Journal of Advanced Transportation)
Secondary raw materials (SRMs) tend to be a valuable replacement for finite virgin materials especially since construction works (i.e., building and civil engineering work such as road construction) require vast quantities of raw materials. Using SRM originating from recycling a broad range of inorganic waste materials (e.g., mining waste, different industrial wastes, construction, and demolition waste) has been recognized as a promising, generally more cost-efficient, and environmentally friendly alternative to the exploitation of natural resources. Despite the benefits of using SRM, several challenges need to be addressed before using SRM even more. One of them is the long-term durability and little-known response of construction works built using such alternative materials. In this paper, we present the activities to establish a fully functioning digital twin (DT) of a road constructed using SRM. The first part of the paper is devoted to the theoretical justification of efforts and ways of establishing the monitoring systems, followed by a DT case study where an integrated data environment synthesizing a Building Information Model and monitored data is presented. Although the paper builds upon a small scale, the case study is methodologically designed to allow parallels to be drawn with much larger construction projects.